Inactivation of Cell Division Protein FtsZ by SulA Makes Lon Indispensable for the Viability of a ppGpp 0 Strain of Escherichia coli - Nazir, Aanisa; Harinarayanan, Rajendran (Journal of bacteriology, 2016)
The modified nucleotides (p)ppGpp play an important role in bacterial physiology. While the accumulation of the nucleotides is vital for adaptation to various kinds of stress, changes in the basal level modulates growth rate and vice versa. Studying the phenotypes unique to the strain lacking (p)ppGpp (ppGpp 0 ) under overtly unstressed growth conditions may be useful to understand functions regulated by basal levels of (p)ppGpp and its physiological significance. In this study, we show that the ppGpp 0 strain, unlike the wild type, requires the Lon protease for cell division and viability in LB. Our results indicate the decrease in FtsZ concentration in the ppGpp 0 strain makes cell division vulnerable to SulA inhibition. We did not find evidence for SOS induction contributing to the cell division defect in the ppGpp 0 Δ lon strain. Based on the results, we propose that basal levels of (p)ppGpp are required to sustain normal cell division in Escherichia coli during growth in rich medium and that the basal SulA level set by Lon protease is important for insulating cell division against a decrease in FtsZ concentration and conditions that can increase the susceptibility of FtsZ to SulA. IMPORTANCE The physiology of the stringent response has been the subject of investigation for more than 4 decades, with the majority of the work carried out using the bacterial model organism Escherichia coli . These studies have revealed that the accumulation of (p)ppGpp, the effector of the stringent response, is associated with growth retardation and changes in gene expression that vary with the intracellular concentration of (p)ppGpp. By studying a synthetic lethal phenotype, we have uncovered a function modulated by the basal levels of (p)ppGpp and studied its physiological significance. Our results show that (p)ppGpp and Lon protease contribute to the robustness of the cell division machinery in E. coli during growth in rich medium.